(untitled) (Bangladesh Journal of Botany, 2023)
In the present study effects of different plant growth regulator combinations on leaf callus growth in two Rosa hybrida cultivars, Rosa hybrida ‘Ingrid Bergman’ and Rosa hybrida ‘Xindongfang’, were analyzed. The plant growth regulators were added into MS, MS + 2,4-D (1.5 mg/l, 2.5 mg/l, 3.5 mg/L, and 4.5 mg/l) and MS + 2.0 mg/l NAA + 1.0 mg/l ZT, MS + 2.0 mg/l NAA + 1.0 mg/l KT, MS + 2.0 mg/l NAA + 1.0 mg/l 6-BA and MS + 2.0 mg/l NAA. The leaves were treated as broken and cultured on these nine different media types. Results showed significant differences in color, morphology, and callus quantity. In the first medium, the callus of rose leaves was the best on MS + 4.5 mg/l 2,4-D medium, followed by MS + 2.5 mg/l 2,4-D and MS + 3.5 mg/l 2,4-D, and finally MS + 1.5 mg/l 2,4-D. No callus was found in MS medium. In the second kind of medium, the leaves grow callus, and the callus grew best on MS + 2.0 mg/l NAA + 1.0 mg/l ZT medium, followed by MS + 2.0 mg/l NAA + 1.0 mg/l KT, finally MS + 2.0 mg/l NAA + 1.0 mg/l 6-BA, MS + 2.0 mg/l NAA medium, the callus grew loose and dry, and lost luster after a few days. Therefore, 2,4-D, KT, ZT, 6-BA, and NAA can promote the formation of callus. With the increase of concentration of 2,4-D, the callus induction rate increased, and the color of the callus also changed significantly. The combination of KT, ZT, and NAA had an obvious effect on callus induction and expansion. Bangladesh J. Bot. 52(3): 867-873, 2023 (September)